P051: Interventions to improve emergency department consultation processes: a systematic review. (May 2019) - Gaudet, L.; Kirkland, S.; Keto-Lambert, D.; Rowe, B.
Abstract : Introduction : Emergency Department (ED) consultations are often necessary for safe and effective patient care. Delays in throughput related to ED consultations can increase a patient's ED length of stay (LOS) and contribute to ED crowding. This review aimed to characterize and evaluate interventions to improve consultation metrics.Methods : Eight primary literature databases and the grey literature were comprehensively searched. Comparative studies of interventions to improve ED consultation metrics were included. Unique citations were screened for relevance and the full-texts of relevant articles were reviewed by two independent reviewers. Data on study characteristics and outcomes were extracted in duplicate onto standardized forms. Disagreements were resolved through consensus. Categorical variables are reported as proportions. Continuous variables are reported as the median of the means and total range.Results : After screening 2632 unique citations and 19 from the grey literature items, 24 studies were included. Seventeen interventions targeted specific conditions or speciality services, while the remainder targeted all ED presentations. Interventions fell into three broad categories: strategies to expedite patient care, including clinical pathways (42%); interventions to improve consultant responsiveness (33%); and addition of a specialized care team to the ED (25%). Overall, eight studies reported on the overall proportion of consults in the ED, of which six reported an increase in the consultation proportion (median: +0.6%, range: −11.3% to +49.6%). Six studies reported the proportion of consulted patients who were admitted, of which four reported an increase (median: +1.1%, range: −5.9% to +3.5%). On the other hand, six of seven studies reporting on time from request to consult arrival reported a decrease (median: −25 minutes, range: −66 to +3.8 minutes). Similarly, overall ED LOS was reported to be lower in 17/19 studies reporting this metric (median: −47.6 minutes, range: −600 minutes to +59 minutes).Conclusion : A variety of strategies have been employed to improve ED consultation processes and outcomes. Neither the proportion of consulted patients in the ED nor the proportion of admissions were improved; however, interventions appeared successful at improving consultant arrival times and overall ED LOS. Improvements in consultation processes may be an effective strategy to improve ED throughput and thereby reduce ED crowding.